Phosphorus in soils of riparian and non-riparian wetland and buffer strips in the Waikato area, New Zealand - Aye, Tin Maung; Nguyen, ML; Bolan, NS; Hedley, MJ (Informa UK Limited, 2006)
This paper examines the potential for phosphorus (P) release from intensively grazed pasture to waterways. In particular it describes the P release processes occurring in riparian buffer strips. Soil samples at three depths (0 2.5, 2.5 7.5, and 7.5 15 cm) were collected from riparian buffer strips, including wetland and non?riparian areas at three pasture sites. These soil samples were analysed for total P, plant available P as measured by Olsen P, and soil solution P as measured by 0.01M CaCl2?extractable P. The P retention capacity and P buffering capacity of the riparian soils were also measured. A significant relationship was found between Olsen P and 0.01M CaCl2?extractable soil P, indicating that soils with a high plant available P pool (measured as Olsen P) potentially have a high P loss in subsurface flow (as represented by CaCl2?extractable P). All of the CaCl2?P concentrations in the top 2.5 cm soil depth at the study sites were higher than the threshold concentration (0.01 mg CaCl2?P litre 1) considered to stimulate fresh water algal growth. This P could contribute to P losses through leaching and surface runoff. However, soils at lower depths (2.5 7.5 and 7.5 15 cm) were found to have higher P sorption and higher P buffering capacity, thus potentially can trap more (15 45 kg P ha 1) than the surface profile (0 2.5 cm). Subsoils may therefore play an important role in controlling P release. The P release may vary depending on the P sorption characteristic of soils and flow pathways. Development of riparian buffer strips for an effective decrease in P losses from intensively grazed systems should take into account P release characteristics of the soil, the distribution of P in soil profile, and the time necessary for plant available P (i.e., Olsen P) to decline to acceptable levels.